2019
DOI: 10.1186/s13071-019-3552-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of anopheline feeding/resting behaviour and Plasmodium infections in North Cameroon, 2011–2014: implications for malaria control

Abstract: Background Effective malaria control relies on evidence-based interventions. Anopheline behaviour and Plasmodium infections were investigated in North Cameroon, following long-lasting insecticidal net (LLIN) distribution in 2010. Methods During four consecutive years from 2011 to 2014, adult mosquitoes were collected indoors, outdoors and in exit traps across 38 locations in the Garoua, Pitoa and Mayo-Oulo health districts. Anophelines were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 50 publications
1
36
2
Order By: Relevance
“…gambiae was the main species collected in both sites. Female Anopheles mosquitoes regularly take blood meal every 3 days to mature their eggs and owing to this obligation and depending on the cues smelt, they need to enter to human habitats or animal housing [6][7][8]. During this study, LFET prevented and protected people from a signi cant proportion of unfed female mosquitoes likely searching a blood meal, 39% of total An.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…gambiae was the main species collected in both sites. Female Anopheles mosquitoes regularly take blood meal every 3 days to mature their eggs and owing to this obligation and depending on the cues smelt, they need to enter to human habitats or animal housing [6][7][8]. During this study, LFET prevented and protected people from a signi cant proportion of unfed female mosquitoes likely searching a blood meal, 39% of total An.…”
Section: Discussionmentioning
confidence: 97%
“…Malaria parasite transmission is mediated by females of Anopheles mosquitoes in Sub-Saharan of Africa. These female mosquitoes to have progeny and survive, need to seek for blood meal in order to lay eggs, and that blood meal takes place most of the time late and indoors on humans [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of malaria control, the use of physical barriers (nets on windows and doors) as well as the insecticide action, induce a stress in anopheline mosquitoes interfering with blood feeding or with resting on interior walls until their eggs are fully matured. Studies indicate that behavioral modi cations could include a change in feeding times, a switch from feeding exclusively on humans to feeding on other animals or an increase in the exophilic behavior [71]. These behavioral changes could rise due to selection pressure induced by LLINs and IRS and lead to mosquito vectors feeding at earlier times and/or in the peridomicile or extra-domiciles.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria transmission is mediated by female Anopheles mosquitoes. Female mosquitoes seek blood meals late at night in human dwellings [6][7][8], where they are vulnerable. Although malaria is mostly transmitted indoors, some studies in East and West Africa have shown malaria transmission occurring outdoors by mosquitoes that escape insecticides or other indoor control methods [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%